2012
DOI: 10.1684/mrh.2012.0315
|View full text |Cite
|
Sign up to set email alerts
|

The effects of magnesium sulphate on desflurane requirement, early recovery and postoperative analgesia in laparascopic cholecystectomy

Abstract: Purpose: we evaluated the effects of magnesium sulphate infusion on anesthetic requirement, early recovery and postoperative analgesia in desflurane-remifentanil-based, balanced anaesthesia. Methods: 60, ASA (American Society of Anesthesiologists) group 1-2 patients who were scheduled for laparoscopic cholecystectomy were randomly divided into two groups. Before anesthesia, the magnesium-treated group (n = 30) received a 15 min infusion of 40 mg/kg of magnesium sulphate followed by 10 mg/kg/h by continuous i.v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…In 8 trials, a perioperative use of ketamine was administered [11,[22][23][24][25][26][27][28]. In 5 trials, a preoperative bolus of magnesium sulfate was followed by a continuous infusion throughout surgery [29][30][31][32][33]. In 1 trial, a preoperative amantadine was administrated [34].…”
Section: Systematic Searchmentioning
confidence: 99%
“…In 8 trials, a perioperative use of ketamine was administered [11,[22][23][24][25][26][27][28]. In 5 trials, a preoperative bolus of magnesium sulfate was followed by a continuous infusion throughout surgery [29][30][31][32][33]. In 1 trial, a preoperative amantadine was administrated [34].…”
Section: Systematic Searchmentioning
confidence: 99%
“…17 Infusion of MgSO 4 at a rate of 10 mg/kg/h to humans undergoing cholecystectomy resulted in a 2-fold increase in serum Mg concentrations and was associated with a decrease in desflurane MAC of 20%. 6 In another study, 8 MgSO 4 infusion at a rate of 8 mg/kg/h decreased propofol dose requirements by 50% and resulted in a 35% increase in baseline serum Mg concentrations. In dogs undergoing elective surgery, infusion of MgSO 4 at a rate of 12 mg/kg/h increased serum Mg concentrations and resulted in a decreased requirement for halothane.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, MgSO 4 infusion (12 mg/kg/h) significantly reduced the requirement for halothane in dogs undergoing elective ovariohysterectomy in 1 study, 17 but a higher administration rate (15 mg/kg/h) failed to reduce the isoflurane requirement in dogs undergoing a similar surgical procedure 29 and did not change the MAC of isoflurane in goats. 30 Other studies in humans have reported that MgSO 4 infusion decreased desflurane requirements, 6,7 whereas it increased requirements for sevoflurane. 32 The study reported here had some potentially limiting factors that may have influenced the results.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations